2010
DOI: 10.1186/1472-6874-10-11
|View full text |Cite
|
Sign up to set email alerts
|

Are treatments for cervical precancerous lesions in less-developed countries safe enough to promote scaling-up of cervical screening programs? A systematic review

Abstract: BackgroundSince the mid-1990s, there have been growing efforts to prevent cervical cancer in less-developed countries through the development of innovative screening approaches such as visual inspection of the cervix associated with same day management of cervical lesions with cryotherapy or loop electrosurgical excision procedure (LEEP). In the past, promising cancer screening interventions have been widely promoted despite incomplete evidence, only to become the subject of intense controversies about ensuing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
2
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 63 publications
4
40
2
3
Order By: Relevance
“…A review of available evidence suggests that cryotherapy is not associated with excess harm in resource-limited settings when performed by qualified providers, but data are insufficient for women of reproductive age. 28 Also, speculatively, the ablation of the squamocolumnar junction may reduce future risk of acquiring a new HPV infection that could progress to cancer. 29 We note that, due to the low specificity of local pathology diagnoses, most women in the CM cohort who received colposcopy were referred to treatment; thus, the potential for overtreatment exists with both management strategies.…”
Section: Discussionmentioning
confidence: 99%
“…A review of available evidence suggests that cryotherapy is not associated with excess harm in resource-limited settings when performed by qualified providers, but data are insufficient for women of reproductive age. 28 Also, speculatively, the ablation of the squamocolumnar junction may reduce future risk of acquiring a new HPV infection that could progress to cancer. 29 We note that, due to the low specificity of local pathology diagnoses, most women in the CM cohort who received colposcopy were referred to treatment; thus, the potential for overtreatment exists with both management strategies.…”
Section: Discussionmentioning
confidence: 99%
“…This inexpensive and technically simple technique destroys abnormal tissue by freezing it with a probe cooled by liquid carbon dioxide (CO 2 ). A systematic review of 32 studies found that the procedure is safe and has an overall cure rate of almost 90% (Castro et al, 2003), and more recent studies have confirmed its effectiveness Luciani et al, 2008;Chamot et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Adverse effects after cryotherapy are relatively uncommon and generally minor, reported in 1-2% of women (Cirisano 1999;Nene 2008). Discomfort usually resolves within a week after treatment (Chamot 2010;). Significant bleeding after cryotherapy is uncommon.…”
Section: Other Resources Neededmentioning
confidence: 99%